Development Of Demi-Span Equations For Predicting Height In Institutionalised Malaysian Elderly - Ngoh, Hooi Jiun (2012)
Demi-span measurement can be used as an alternative method to predict height for elderly people. However, there is little data on the accuracy of this method to be used in institutionalised Malaysian elderly. Therefore, the objectives of this study were (1) to determine the anthropometric differences among gender, ethnicity and age groups in institutionalised elderly; (2) to develop a demi-span equation for predicting height in institutionalised elderly; (3) to evaluate the accuracy of published demi-span equations derived from younger adults; and (4) to assess the accuracy of the body mass index (BMI) calculated using the predicted height from published demi-span equations and that from the new equation developed in this study.